2016
DOI: 10.1097/md.0000000000003376
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Reduction, Discectomy, and Three Cortical Iliac Bone Grafting With Instrumentation to Treat A Huge Tear Drop Fracture of the Axis

Abstract: Fractures of the axis body have been little reported and treatment strategies remain controversial and individualized. Not more than 10 cases of huge tear drop fracture of the axis (HTDFA) have been reported in previous studies and the treatment method varies from conservative treatment to an anterior, or posterior, approach surgery. Considering the sparse knowledge of HTDFA, we present a special case report to share our experience and to explore the safety and effectiveness of anterior reduction and fusion to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 13 publications
(17 reference statements)
0
9
0
Order By: Relevance
“…They reported that all C2 tear drop fractures were well treated with conservative treatment [ 19 ]. On the other hand, a few case reports have described surgical treatments for huge or large-sized anterior C2 TD fractures [ 9 , 10 , 11 , 12 , 13 , 14 ]. According to the review of the literature, as the fracture displacement of C2 increased, the proportion of nonunion after conservative treatment increased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported that all C2 tear drop fractures were well treated with conservative treatment [ 19 ]. On the other hand, a few case reports have described surgical treatments for huge or large-sized anterior C2 TD fractures [ 9 , 10 , 11 , 12 , 13 , 14 ]. According to the review of the literature, as the fracture displacement of C2 increased, the proportion of nonunion after conservative treatment increased.…”
Section: Discussionmentioning
confidence: 99%
“…However, a close analysis of previous studies showed that anterior C2 TD fractures successfully managed with conservative treatment were small-sized or simple anterior TD fractures. Furthermore, a few case reports have suggested that if anterior C2 TD fractures are huge or massive, it is better to reconstruct the anterior column through surgery [ 9 , 10 , 11 , 12 , 13 , 14 ]. However, the exact criteria for determining indications for surgical treatment of large-sized anterior C2 TD fractures have not been provided and are controversial.…”
Section: Introductionmentioning
confidence: 99%
“…When the hyperextension of the cervical spine occurs, the odontoid process of the axis acts as a moment arm of leverage to transfer the backward stress, the posterior elements of axis acts as a fulcrum. At this moment, extension of the anterior longitudinal ligament could cause the avulsion fracture at anterior inferior portion of the axis body and various degrees of injury of the anterior longitudinal ligament [9][10]. The hyperextension has also leaded to intervertebral disc injury and C2/3 instability in this patient.…”
Section: Discussionmentioning
confidence: 99%
“…There is lots of controversy over the conservative and surgical methods because both seems to be effective in the treatment of HTDFA. Due to the lack of reducement completely with skull traction or cervical collar, the fracture bone fragment usually had healed with significant malunion when choosing conservative management [10]. Furthermore, the HTDFA could cause the compression of esophagus and induce the dysphagia during conservative treatment in some patients [11].…”
Section: Discussionmentioning
confidence: 99%
“…In some cases the huge tear-drop fracture fragments of the C2 vertebra can cause direct esophagus compression consequently leading to dysphagia. [24] The posterior approach surgery is also not free from postoperative dysphagia in Hangman fracture patients. Our results demonstrate that the incidence of dysphagia after the posterior surgical approach in Hangman fracture patients was 10.0% (1 of 10 patients), which was similar to previous studies.…”
Section: Discussionmentioning
confidence: 99%